Application for Proteomic Techniques in Studying Osteoarthritis: A Review - Gharbi, Myriam; Deberg, Michelle; Henrotin, Yves (Frontiers in Physiology, 2011)
After the genomic era, proteomic corresponds to a wide variety of techniques to study the protein content of cells, tissue or organism and to isolate protein of interest. It offers the choice between gel-based and gel-free methods or shotgun proteomics. Applications of proteomic technology may concern three principal objectives in several biomedical or clinical domains of research as in osteoarthritis: (i) to understand the physiopathology and underlying mechanisms leading to a disease or associated to a particular model, (ii), to find disease-specific biomarker and (iii) to identify new therapeutic targets. This review aimed at gathering most of the data regarding the proteomic techniques and their applications to arthritis research. It also reported technical limitations and solutions, as for example for sample preparation. Proteomics open wide perspectives in biochemical research but many technical matters still remain to be solved.